2007
DOI: 10.1002/hbm.20356
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for neural accommodation to a writing system following learning

Abstract: Native English speakers with no knowledge of Chinese were trained on 60 Chinese characters according to one of three mapping conditions: orthography to pronunciation and meaning (P þ M), orthography to pronunciation (P), and orthography to meaning (M). Following the training, fMRI scans taken during passive viewing of Chinese characters showed activation in brain regions that partially overlap the regions found in studies of skilled Chinese readers, but typically not found in alphabetic readers. Areas include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
97
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 45 publications
16
97
1
Order By: Relevance
“…In our study, we observed activation during character reading near this same ''Chinese region,'' at the left dorsal inferior frontal gyrus (BA9). The peak was at (À50, 2, 34), very close to the peaks of (À48, 4, 35) and (À44, 4, 33) for learners in Nelson et al (2009) and Liu et al (2007), respectively, and to the peaks of (À48, 9, 30) and (À46, 8, 34) for native Chinese speakers in Bolger (2005) and Cao (2010), respectively. This convergence of findings suggests that English speakers can adopt the procedures of addressed retrieval of phonology and semantics after only a short period learning Chinese.…”
Section: Differences Between Chinese and Englishsupporting
confidence: 51%
See 1 more Smart Citation
“…In our study, we observed activation during character reading near this same ''Chinese region,'' at the left dorsal inferior frontal gyrus (BA9). The peak was at (À50, 2, 34), very close to the peaks of (À48, 4, 35) and (À44, 4, 33) for learners in Nelson et al (2009) and Liu et al (2007), respectively, and to the peaks of (À48, 9, 30) and (À46, 8, 34) for native Chinese speakers in Bolger (2005) and Cao (2010), respectively. This convergence of findings suggests that English speakers can adopt the procedures of addressed retrieval of phonology and semantics after only a short period learning Chinese.…”
Section: Differences Between Chinese and Englishsupporting
confidence: 51%
“…Liu et al (2007) and Nelson et al (2009) found that learners showed greater activation in right fusiform gyrus and left dorsal inferior frontal gyrus for Chinese characters than English words, suggesting they accommodate the special features of Chinese during learning. These results allow a general conclusion about accommodation when writing was not a part of instruction.…”
Section: Introductionmentioning
confidence: 97%
“…This association must be learned by rote memorization of Chinese characters, demanding an intensive coordination of various kinds of linguistic information contained in written Chinese (28,(30)(31)(32)(33)(34)(35). The left middle frontal gyrus is thought to be involved in the allocation and coordination of cognitive resources in working memory (36,37) and may therefore be recruited to serve this function (34,35,38).…”
Section: Discussionmentioning
confidence: 99%
“…These differences can lead to differences in how reading is supported in the brain. Readers of Chinese show relatively more engagement of visuospatial areas and left middle frontal regions for verbal working memory, presumably for recognizing complex, square-shaped characters whose pronunciations must be memorized by rote instead of being learned by using letter-to-sound conversion rules (31)(32)(33)(34)(35). In an fMRI study, we previously showed that, unlike impaired reading in English and other Western languages, impaired reading in logographic Chinese is associated with functional disruption of processes localized to the left middle frontal gyrus (28).…”
mentioning
confidence: 99%
“…It is worth mentioning that previous studies documented the word specificity of N170 in the left hemisphere; we found the sensitivity of N170 to character likeness in both hemispheres, which indicated that the property of character likeness would not modulate the lateralization. One explanation, as mentioned earlier, is that pictographs elicited bilateral activations, which reflected the greater visuospatial analysis, because of years of experience in processing Chinese characters (a script that relies on visuospatial analysis and consequently recruits the right hemisphere; Liu, Dunlap, Fiez, & Perfetti, 2007;Tan, Laird, Li, & Fox, 2005;Tan et al, 2000). Second, the present study found that the latencies of N170, but not P100, were also tuned to character likeness with shorter latencies to more character-like stimuli, although the results were not entirely consistent across the two hemispheres and across the two types of evaluation data of character likeness.…”
Section: Tuning Of N170 To Character Likenessmentioning
confidence: 96%